KEDUDUKAN TAFSIR KAUNIAH ILMI DALAM TAFSIR AL-QUR’AN - Suri, Sufian (Liwaul Dakwah: Jurnal Studi Keislaman, 2019)
In the Qur'an there are verses that show various scientific realities so that it gives impetus to humans to discuss and explore them. Since ancient times some Muslims have tried to create the closest relationship between the Qur'an and science. Such efforts turned out to be increasingly widespread in the future, and have brought many benefits. The interpretation of the Qur'an continues to develop in accordance with the development of science, and it turns out to have an effect on the ayat of the Qur'an, especially the ayat of Kauniyah,interpreters try to prove that the content of the Qur'an will never be in contrary to modern science. As a result of human work, diversity in the mode of interpretation emerges inevitably.Various factors can lead to a variety of patterns, both differences in tendencies, interests and motivation of commentators, differences in the mission carried, differences in the depth and variety of knowledge mastered, differences in situations and conditions encountered, and other. All of that gives rise to features which then develop into large streams in the interpretation of the Qur'an. The interpretation of the Qur'an is always colored by the thoughts of the mufassir, a mufassir who wrestles and pursues studies of science, then his interpretation is always associated with modern scientific theories which in their development are called "ilmi" interpretations.